The Role of Local Orientations Gradients in the Formation of the Recrystallisation Texture in Cold-Rolled If Steel - Castro-Cerda, F (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
This study investigates the subsequent stages of recrystallisation in Interstitial-Free (IF) steel subjected to an unconventional continuous annealing process with a controlled thermal gradient. A cold-rolled steel strip was exposed to varying annealing temperatures along its length, enabling the analysis of microstructural evolution during the course of recrystallisation. The microstructure and stored energy were assessed at various positions along the strip using Electron Backscatter Diffraction (EBSD). The results underscore the significant influence of local misorientation and structural inhomogeneity on orientation selection during recrystallisation. The remaining non-recrystallised volume fraction (NRF) strongly correlates with the average misorientation gradient, obeying a phenomenological power-law correspondence with an exponent of ~3.7. This indicates that the recrystallisation process is highly sensitive to small changes in local orientation gradients. These findings highlight the crucial role of stored energy distribution for texture evolution, particularly during the early stages of recrystallisation in continuous annealing. It is observed that g-fiber grains, in comparison to a-fiber grains, are much more susceptible to grain fragmentation and therefore develop more robust intra-granular misorientation gradients, allowing for successful nucleation events to occur. In the present study, these phenomena are documented in a statistically representative manner. These insights are valuable for optimising thermal processing in interstitial-free (IF) steels. © 2025 by the authors.